Atmospheric Nitrous Oxide Variations on Centennial Time Scales During the Past Two Millennia. Issue 9 (8th September 2020) - Ryu, Y.; Ahn, J.; Yang, J.‐W.; Brook, E. J.; Timmermann, A.; Blunier, T.; Hur, S.; Kim, S.‐J.
Abstract: The continuous growth of atmospheric nitrous oxide (N2 O) is of concern for its potential role in global warming and future stratospheric ozone destruction. Climate feedbacks that enhance N2 O emissions in response to global warming are not well understood, and past records of N2 O from ice cores are not sufficiently well resolved to examine the underlying climate‐N2 O feedbacks on societally relevant time scales. Here, we present a new high‐resolution and high‐precision N2 O reconstruction obtained from the Greenland NEEM (North Greenland Eemian Ice Drilling) and the Antarctic Styx Glacier ice cores. Covering the N2 O history of the past two millennia, our reconstruction shows a centennial‐scale variability of 10 ppb. A pronounced minimum at 600 CE coincides with the reorganizations of tropical hydroclimate and ocean productivity changes. Comparisons with proxy records suggest association of centennial‐ to millennial‐scale variations in N2 O with changes in tropical and subtropical land hydrology and marine productivity. Plain Language Summary: Nitrous oxide (N2 O) is a greenhouse and ozone‐depleting gas. The growing level of N2 O in the atmosphere is of global concern, and records of past N2 O variations can provide an important context for understanding the links between N2 O and climate change. In this study, we report new, high‐quality N2 O records covering the last two millennia using ice cores obtained from Greenland and Antarctica. Our N2 O records show rapid centennial‐scale changes in atmospheric N2 O and confirm a pronounced minimum near 600 CE. Comparison with climate records suggests that hydroclimate change on land and changes in marine productivity contribute to centennial‐ to millennial‐scale N2 O variations. Key Points: We report records of N2 O concentration for the last 2, 000 yr from the Styx ice core in Antarctca and NEEM ice core in Greenland The data accurately reveal the timing and magnitude of N2 O variations on centennial time scales Variations in N2 O are associated with changes in tropical and subtropical land hydrology and marine productivity